PROSES KREATIF PENCIPTAAN MOTIF BATIK SEBAGAI MEDIA PEMBELAJARAN SENI BERBASIS BUDAYA LOKAL DI SEKOLAH DASAR - Ramadhanti, Adinda Asri; Putera, Rafhi Febryan; Ramayani, Neti; Zohro, Miftahus Silmi (Jurnal PGSD, 2025)
This article discusses the creative process in the creation of batik motifs as a learning medium for local culture-based art in elementary schools. Art learning through batik is seen as one of the effective approaches to develop creativity, cultural appreciation, and fine motor skills of students. This article focuses on the study of the creative process of creating batik motifs as a learning medium, the stages of the creative process which include the exploration of ideas, motif design and reflection of the work. Through an experiential learning pedagogical approach, students are given the opportunity to understand local cultural values while expressing their visual ideas freely and in a directed way. The motifs developed refer to regional cultural symbols, such as flora, and traditional geometric shapes, which are then processed into batik designs that are relevant to the aesthetic characteristics of elementary school children. This study uses a qualitative descriptive method, which is carried out through a literature review and reflection on the author's experience in participating in batik design workshops. The creative process studied includes the stages of preparation, incubation, illumination, and verification, all of which are relevant to be applied in fine arts learning. In this study, it is shown that integrating batik as a learning medium can develop visual skills, instill a sense of cultural love, and form characters such as perseverance, appreciation, and creativity. Therefore, the creative process of making batik can be an effective learning strategy in the context of the Independent Curriculum.